Layanan Klasikal Bimbingan Karier dengan Media PPT Berbasis Object Superiority Effect untuk meningkatkan Pemahaman Diri dan Pemahaman Karier Siswa SMA - Hartono, Hartono; Musdalifah, Ana (Jurnal Bimbingan dan Konseling Terapan, 2019)
Self- knowledge and career knowledge of high school students are important aspects that need to be improved. This study aims to determine the significance of improvement in aspects of self-knowledge and career knowledge aspects of high school students through the classical service of career guidance using PowerPoint media based on object superiority effects, which was designed using the one-cycle classroom action research method in the students population of class XII of ITP high school at Surabaya city with a sample of 78 students taken by random class techniques. The research data was collected using the scale of students' self-knowledge and the scale of students' career knowledge. The research data were analyzed using parametric statistical t test techniques with the help of the SPSS for Windows version 23.0 program. The results of the data analysis of students’ self-knowledge obtained a value of t = -.399 at a significant level of .691 which means not significant, while the results of data analysis of students' career knowledge obtained a value of t = -1.758 at a significant level of .081, which also means insignificant. The results of this study indicate that the classic service actions of career guidance using PowerPoint media based on object superiority effects significantly cannot improve self-knowledge and career knowledge of high school students. Based on the results of this study, it is recommended that further research be conducted by using integrated guidance and counseling services in an effort to improve self- knowledge and career knowledge of high school students.